Filsafat Hukum Dalam Perspektif Aksiologi - Ramdani Abd. Hafizh; Masadah (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2026)
Legal philosophy, as a branch of philosophy, plays a crucial role in understanding the nature, objectives, and fundamental values underlying law. One philosophical branch closely related to legal philosophy is axiology, which is the theory of values. This article aims to analyze the relationship between legal philosophy and axiology within the context of legal thought, as well as to examine how axiological values are reflected in the processes of legislation and legal decision-making. This study employs a normative juridical research method with a philosophical approach, analyzing concepts, doctrines, and scholarly perspectives concerning legal philosophy and axiology. The findings indicate that legal philosophy and axiology are complementary and inseparable, as axiological values such as justice, truth, freedom, and humanity serve as fundamental foundations in the formation, application, and enforcement of law. These values function not only as moral principles but also as practical guidelines for policymakers and law enforcement officials in legislative processes and legal decision-making. Therefore, a comprehensive understanding of axiological aspects in legal philosophy is essential to realize a legal system that is just, humane, and aligned with the values upheld by society.